Improving bandwidth utilization by compressing small-payload traffic for vehicular networks - Jianan Sun; Ping Dong; Yajuan Qin; Tao Zheng; Xiaoyun Yan; Yuyang Zhang (International Journal of Distributed Sensor Networks)
The low bandwidth utilization is a serious problem for mobile services over vehicular networks. This is mainly resulted from the high-rate transmission of packets carrying small payloads. Some solutions are proposed to forward packets by context identifier, instead of IP address, based on header compression and software-defined networking technology. However, these solutions cannot be deployed in vehicular networks successfully, due to the limitations on processing capacity and routing scalability. In this article, we propose a scalable end-to-end header compression scheme, which takes advantage of the locator/identifier separation concept and some characteristics of software-defined networking. We propose to utilize a forwarding identifier to indicate the compressor’s location, separating the header compression process from the packet forwarding process. In this way, context identifiers with an identical value are allowed to coexist in the same network, and flow table entries matching the compressed flows can be aggregated. Extensive simulations have been conducted and the results demonstrate that scalable end-to-end header compression experiences outstanding performances in bandwidth utilization and delay, showing its greater suitability for vehicular network transmission optimization.